Respuesta :
Here: 4x - 3y = 15
2x + 2y = 4
[ Multiply 2nd equation by 2, ]
4x + 4y = 8
Now, Subtract 1st from 2nd,
7y = -7
y = -1
Substitute it in 2nd equation,
2x + 2(-1) = 4
2x = 4 + 2
x = 6/2
x = 3
In short, Your Answer would be (3, -1)
Hope this helps!
2x + 2y = 4
[ Multiply 2nd equation by 2, ]
4x + 4y = 8
Now, Subtract 1st from 2nd,
7y = -7
y = -1
Substitute it in 2nd equation,
2x + 2(-1) = 4
2x = 4 + 2
x = 6/2
x = 3
In short, Your Answer would be (3, -1)
Hope this helps!
Answer:
3 and -1
Step-by-step explanation: took the 1.08 test